Sacrifice : a gold star widow's fight for the truth - Black, Michelle Richmond (G.P. Putnam's Sons, 2021)
Drawing on exclusive interviews with the survivors of her husband's unit, research into the military leadership and accountability and her own unique vantage point as a gold star widow, the author sets out to find the truth behind her Green Beret husband's death.